A GIS Approach to Identifying Tourism Potential Across Varied Landscapes: A Case Study in West Lombok Regency - Siwantari, Putu Ayu Pratiwi Duta; Gede, I Putu; Pati, Indra (Bali Journal of Hospitality, Tourism and Culture Research, 2024)
The identification of potential tourist attractions is essential for understanding the tourism assets within mountain, plain, and coastal villages in North Lombok Regency. This study aims to assess these potentials using Geographic Information System (GIS) technology and location quotient (LQ) analysis. An exploratory methodology with stratified random sampling was employed. The findings indicate that Bayan Subdistrict villages exhibit strong potential for mountain-based tourism, while Tanjung Subdistrict villages are well-suited for coastal tourism development. The diverse natural, cultural, and man-made resources across these regions can be enhanced through effective promotional strategies and stakeholder involvement. Leveraging unique local characteristics and products can position these villages toward independent and sustainable tourism development, contributing to competitive advantages in the tourism sector.